Preparation method of water-resistant spherical aluminum nitride-boron nitride composite powder
Through high-temperature hydrothermal reaction and high-temperature carbon reduction method of nanocarbon replacement oxygen element, combined with the hydrolysis of silane coupling agent and the reaction of resin, a water-resistant spherical aluminum nitride-boron nitride composite powder was successfully prepared, solving the problem of easy hydrolysis of existing powders in humid environments and improving the durability and applicability of their applications.
Patent Information
- Application Number
- CN202411794430.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The existing aluminum nitride-boron nitride composite powders are prone to hydrolysis in air or humid environments, resulting in a decrease in thermal conductivity and changes in physical and chemical properties, limiting their application range.
Aluminum nitride-boron nitride precursor is generated by high-temperature hydrothermal reaction, and spherical precursor is formed by spray granulation, and then a high-temperature carbon reduction method of nanocarbon displaced oxygen elements is carried out in nitrogen or ammonia to convert it into a spherical aluminum nitride-boron nitride composite powder. Finally, the surface coating is carried out through the hydrolysis of the silane coupling agent and the reaction of the resin to improve the water resistance of the powder.
The prepared spherical aluminum nitride-boron nitride composite powder has high spherical shape, smooth surface, good fluidity and dispersion, and maintains stable performance in humid environments, extending its service life.
Smart Images

Figure CN119613124A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic non-metallic powder preparation, and specifically relates to a method for preparing water-resistant spherical aluminum nitride-boron nitride composite powder. Background Art
[0002] Exploring the application performance of aluminum and boron-containing nitride powders in high thermal conductivity composite materials has become one of the research hotspots in this field in recent years.
[0003] Aluminum nitride is a covalently bonded compound, belonging to diamond-like nitride, with a hexagonal wurtzite crystal structure. Its in-plane thermal conductivity is about 320W / (m·K), which has a high thermal conductivity. The preparation methods of aluminum nitride powder mainly include direct nitridation, self-propagating high-temperature synthesis, carbon thermal reduction, chemical vapor deposition, high-energy physical assisted method and mechanochemical method. Among them, the direct nitridation method is widely favored for its low energy consumption and simple reaction process, but there are also problems such as low reaction conversion rate and easy agglomeration of powder. Although the self-propagating high-temperature synthesis method can react violently, it is necessary to control the conversion rate and purity of aluminum nitride. In addition, aluminum nitride is easily hydrolyzed in air or humid environment, which not only reduces its thermal conductivity, but also changes its physical and chemical properties, bringing difficulties to the application of aluminum nitride.
[0003] Boron nitride is a high-performance material with a variety of crystal isomers, including hexagonal boron nitride, cubic boron nitride, wurtzite boron nitride, etc. Although boron nitride has many advantages, such as high thermal conductivity, electrical insulation, chemical stability, etc., it also has some limitations and challenges in practical applications. First, although boron nitride has excellent thermal conductivity, its thermal conductivity coefficient in different directions is different, which has formed a certain restriction on its application in the field of thermal conductivity. Secondly, the preparation cost of boron nitride nanosheets is relatively high, which limits its widespread promotion in cost-sensitive application fields.
[0003] In recent years, many studies have been devoted to the development of aluminum nitride-boron nitride composite materials with good dispersibility and high filling capacity. Invention patent CN109384468A discloses a method for preparing a boron nitride-aluminum nitride composite powder, which successfully synthesizes alumina powder and boron nitride semi-finished products into boron nitride-aluminum nitride composite powder in nitrogen, but its particles are easily broken and difficult to promote in practical applications. Invention patent CN104725049A discloses a method for preparing an aluminum nitride / boron nitride composite ceramic powder, which successfully synthesizes aluminum nitride / boron nitride composite ceramic powder by using a carbon thermal reduction method, but its particles have a more serious agglomeration problem, which limits its scope of use. Summary of the invention
[0004] Based on the problems described in the background technology, the purpose of the present invention is to provide a method for preparing water-resistant spherical aluminum nitride-boron nitride composite powder. The prepared composite powder is a spherical powder with a smooth surface and good water resistance. It solves the problems of particle breakage and agglomeration in the prior art and expands its practical application range.
[0005] The present invention provides a method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder, and the specific formation process and principle thereof are as follows: (1) In the reactor process, the boron source and the alkaline nitrogen source undergo a high-temperature hydrothermal reaction to generate a boron nitride precursor, and the aluminum source and the alkaline nitrogen source also undergo a high-temperature hydrothermal reaction to generate an aluminum sol; the aluminum sol has good adhesion and can be uniformly adsorbed on the surface of the boron nitride precursor; after spray granulation treatment, the aluminum nitride-boron nitride precursor slurry is converted into a spherical aluminum nitride-boron nitride precursor. (2) In the atmosphere furnace process, the spherical aluminum nitride-boron nitride precursor is converted into a spherical aluminum nitride-boron nitride composite powder by a high-temperature carbon reduction method in which nano-carbon replaces the oxygen element under nitrogen or ammonia. In this process, yttrium aluminate becomes liquid under high temperature conditions and has a strong bonding effect, making the spherical aluminum nitride-boron nitride particles not easy to break and thus maintaining good sphericity. At the same time, residual carbon can be removed during the low-temperature calcination process. (3) During the surface coating process, the silane coupling agent is hydrolyzed into silanol and undergoes dehydration condensation with the hydroxyl groups on the surface of the spherical aluminum nitride-boron nitride. The resin reacts and combines with the organic functional groups in the silane coupling agent to obtain a water-resistant spherical aluminum nitride-boron nitride composite powder.
[0006] The present invention provides a method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder, comprising the following steps: (1) Preparation of spherical aluminum nitride-boron nitride precursor: a boron source, an aluminum source, a carbon source, an alkaline nitrogen source, and distilled water are transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 300-500°C for reaction for 24-72 hours, and naturally cooled to room temperature to obtain an aluminum nitride-boron nitride precursor slurry, and then a certain amount of yttrium aluminate is poured into the aluminum nitride-boron nitride precursor slurry, mixed evenly, and placed in a spray dryer for granulation to obtain a spherical aluminum nitride-boron nitride precursor; the air inlet temperature of the spray dryer is 200-350°C, the fan frequency is 20-40 Hz, the needle passing time is 1-5 s, and the peristaltic pump speed is 10-30 r / min; (2) Preparation of spherical aluminum nitride-boron nitride composite powder: Add the spherical aluminum nitride-boron nitride precursor obtained in the above (1) into a crucible, and then place the crucible in an atmosphere furnace and calcine it under nitrogen or ammonia at a calcination temperature of 1300-1700° C. for a holding time of 1-12 h, and then calcine it under air at a calcination temperature of 300-600° C. for a holding time of 24-72 h. After the sintered body is naturally cooled to room temperature, it is placed in a planetary ball mill at a rotation speed of 100-300 r / min and ball milled for 5-90 min to obtain a spherical aluminum nitride-boron nitride composite powder; (3) Preparation of water-resistant spherical aluminum nitride-boron nitride composite powder: The spherical aluminum nitride-boron nitride composite powder obtained in the above (2), silane coupling agent, and distilled water are added to a 1000 mL alloy can in a certain proportion, and then placed in a high-speed stirrer, stirred and reacted at room temperature at a speed of 500 to 2000 r / min for 0.5 to 2 h, and then the resin is added to the alloy can in a certain proportion, and the stirring reaction is continued at room temperature at a speed of 500 to 2000 r / min for 0.5 to 2 h, and finally placed in a drying oven at 90 to 150° C. for 12 to 48 h to obtain a water-resistant spherical aluminum nitride-boron nitride composite powder.
[0007] In the step (1), the mass ratio of the boron source, the aluminum source, the carbon source, the alkaline nitrogen source, the distilled water and the yttrium aluminate is 3-10:1-10:3-5:3-10:10-200:0.2-5.
[0008] In the step (1), the boron source is one or more of boric acid, metaboric acid, anhydrous sodium tetraborate, sodium tetraborate pentahydrate, sodium tetraborate decahydrate, and ammonium borate.
[0009] In the step (1), the aluminum source is one or more of aluminum nitrate, aluminum nitrate nonahydrate, aluminum sulfate, aluminum chloride, sodium aluminate, and potassium aluminate.
[0010] The carbon source in step (1) is nano carbon black.
[0011] In the step (1), the alkaline nitrogen source is one or more of ammonia water, cyanuric chloride, melamine, urea and imidourea.
[0012] In the step (1), the yttrium aluminate is one or more of yttrium aluminate and yttrium aluminum stone.
[0013] In the step (2), calcination is carried out under nitrogen or ammonia, and the calcination temperature is 1300-1700°C.
[0014] In the step (3), the mass ratio of the spherical aluminum nitride-boron nitride composite powder, the silane coupling agent, the distilled water and the resin is 300-800:1-6:1-6:1-6.
[0015] The silane coupling agent in step (3) is one or more of: N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, dodecyltrimethoxysilane, dibutylaminomethyltriethoxysilane, 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane, and 3-aminopropylmethyldiethoxysilane.
[0016] The resin in step (3) is one or more of polyamide, polyolefin, polyester, and epoxy resin.
[0017] The present invention has the following technical advantages: (1) The water-resistant spherical aluminum nitride-boron nitride composite powder prepared by the present invention has high sphericity, a smooth surface and no voids, has excellent fluidity and dispersibility in practical applications, and is easy to process and use; secondly, the particle structure of the composite powder is stable and the powder is not easy to break, which greatly improves its durability and reliability in practical use. (2) The present invention realizes the effective coating of spherical aluminum nitride-boron nitride with resin, improves the hydrolysis resistance of the composite powder, enables it to maintain stable performance in a humid environment, and enhances the long-term stability and applicability of the composite powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the water-resistant spherical aluminum nitride-boron nitride composite powder prepared in Example 1.
[0019] Figure 2 This is the SEM image of the product prepared in Comparative Example 1.
[0020] Figure 3 This is the SEM image of the product prepared in Comparative Example 2.
[0021] Figure 4 This is the SEM image of the product prepared in Comparative Example 3.
[0022] Figure 5 This is the SEM image of the product prepared in Comparative Example 4.
[0023] Figure 6 The hydrolysis resistance pH change curve of the powder products prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 is shown. DETAILED DESCRIPTION
[0024] The embodiments described below specifically illustrate the above contents of the present invention, and particularly illustrate that, based on the principles of the present invention, several adjustments and improvements may be made, and these adjustments and improvements are also considered to be within the protection scope of the embodiments of the present invention.
[0025] Example 1 (1) Preparation of spherical aluminum nitride-boron nitride precursor: 30 g of boric acid, 10 g of aluminum nitrate, 30 g of nano-carbon black, 30 g of ammonia water, and 100 g of distilled water were weighed and transferred into a stainless steel reactor lined with polytetrafluoroethylene, and heated at 300° C. for reaction for 24 h. After naturally cooling to room temperature, an aluminum nitride-boron nitride precursor slurry was obtained. Then, 2 g of yttrium aluminate was weighed and poured into the aluminum nitride-boron nitride precursor slurry. After mixing evenly, the mixture was placed in a spray dryer for granulation to obtain a spherical aluminum nitride-boron nitride precursor. The air inlet temperature of the spray dryer was 200° C., the fan frequency was 20 Hz, the needle passing time was 1 s, and the peristaltic pump speed was 10 r / min (the mass ratio of boric acid, aluminum nitrate, nano-carbon black, ammonia water, distilled water, and yttrium aluminate was 30:10:30:30:100:2); (2) Preparation of spherical aluminum nitride-boron nitride composite powder: 300 g of spherical aluminum nitride-boron nitride precursor was weighed and added to a crucible, and the crucible was placed in an atmosphere furnace and calcined under nitrogen at a calcination temperature of 1300° C. for 1 h, and then calcined under air at a calcination temperature of 300° C. for 24 h. After the sintered body was naturally cooled to room temperature, it was placed in a planetary ball mill at a speed of 100 r / min and ball milled for 5 min to obtain spherical aluminum nitride-boron nitride composite powder; (3) Preparation of water-resistant spherical aluminum nitride-boron nitride composite powder: 300 g of spherical aluminum nitride-boron nitride composite powder, 1 g of N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, and 1 g of distilled water were weighed and added into a 1000 mL alloy can according to a certain proportion, and then placed in a high-speed stirrer, stirred and reacted at room temperature at a speed of 500 r / min for 0.5 h, and then 1 g of polyamide was added to the alloy can, and the stirring reaction was continued at room temperature at a speed of 500 r / min for 0.5 h, and finally placed in a drying oven at 90°C for 12 h to obtain water-resistant spherical aluminum nitride-boron nitride composite powder (the mass ratio of spherical aluminum nitride-boron nitride composite powder, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, distilled water, and polyamide was 300:1:1:1).
[0026] Example 2 (1) Preparation of spherical aluminum nitride-boron nitride precursor: 50 g of anhydrous sodium tetraborate, 20 g of aluminum sulfate, 40 g of nano-carbon black, 50 g of cyanuric chloride, and 1000 g of distilled water were weighed and transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 450°C for 48 h, and naturally cooled to room temperature to obtain an aluminum nitride-boron nitride precursor slurry, and then 10 g of yttrium aluminate was weighed and poured into the aluminum nitride-boron nitride precursor slurry. After mixing evenly, the mixture was placed in a spray dryer for granulation to obtain a spherical aluminum nitride-boron nitride precursor; the air inlet temperature of the spray dryer was 300°C, the fan frequency was 30 Hz, the needle passing time was 3 s, and the peristaltic pump speed was 20 r / min (the mass ratio of anhydrous sodium tetraborate, aluminum sulfate, nano-carbon black, cyanuric chloride, distilled water, and yttrium aluminate was 50:20:40:50:1000:10); (2) Preparation of spherical aluminum nitride-boron nitride composite powder: 600 g of spherical aluminum nitride-boron nitride precursor was weighed and added to a crucible, and the crucible was placed in an atmosphere furnace and calcined under nitrogen at a calcination temperature of 1500° C. for 6 h, and then calcined under air at a calcination temperature of 450° C. for 48 h. After the sintered body was naturally cooled to room temperature, it was placed in a planetary ball mill at a speed of 200 r / min and ball milled for 30 min to obtain a spherical aluminum nitride-boron nitride composite powder; (3) Preparation of water-resistant spherical aluminum nitride-boron nitride composite powder: 600 g of spherical aluminum nitride-boron nitride composite powder, 3 g of dodecyltrimethoxysilane, and 3 g of distilled water were weighed and added into a 1000 mL alloy can according to a certain proportion, and then placed in a high-speed stirrer, stirred and reacted at room temperature at 1000 r / min for 1 hour, and then 3 g of polyolefin was added to the alloy can, and the stirring reaction was continued at room temperature at 1000 r / min for 1 hour, and finally placed in a 120°C drying oven for 24 hours to obtain water-resistant spherical aluminum nitride-boron nitride composite powder (the mass ratio of spherical aluminum nitride-boron nitride composite powder, dodecyltrimethoxysilane, distilled water, and polyolefin is 600:3:3:3).
[0027] Example 3 (1) Preparation of spherical aluminum nitride-boron nitride precursor: 100 g of anhydrous sodium tetraborate, 100 g of aluminum sulfate, 50 g of nano carbon black, 100 g of cyanuric chloride, and 2000 g of distilled water were weighed and transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 500 °C for 72 h, and naturally cooled to room temperature to obtain an aluminum nitride-boron nitride precursor slurry. Then 50 g of yttrium aluminate was weighed and poured into the aluminum nitride-boron nitride precursor slurry. The materials are mixed evenly and then placed in a spray dryer for granulation to obtain a spherical aluminum nitride-boron nitride precursor; the air inlet temperature of the spray dryer is 350° C., the fan frequency is 40 Hz, the needle passing time is 5 s, and the peristaltic pump speed is 30 r / min (the mass ratio of anhydrous sodium tetraborate, aluminum sulfate, nano carbon black, cyanuric chloride, distilled water, and yttrium aluminate is 100:100:50:100:2000:50); (2) Preparation of spherical aluminum nitride-boron nitride composite powder: 800 g of spherical aluminum nitride-boron nitride precursor was weighed and added to a crucible, and the crucible was placed in an atmosphere furnace and calcined under nitrogen at a calcination temperature of 1700° C. for 12 h, and then calcined under air at a calcination temperature of 600° C. for 72 h. After the sintered body was naturally cooled to room temperature, it was placed in a planetary ball mill at a speed of 300 r / min and ball milled for 90 min to obtain spherical aluminum nitride-boron nitride composite powder; (3) Preparation of water-resistant spherical aluminum nitride-boron nitride composite powder: 800 g of spherical aluminum nitride-boron nitride composite powder, 6 g of dodecyltrimethoxysilane, and 6 g of distilled water were weighed and added into a 1000 mL alloy can according to a certain proportion, and then placed in a high-speed stirrer, stirred and reacted at room temperature at 2000 r / min for 2 h, and then 6 g of polyolefin was added to the alloy can, and the stirring reaction was continued at room temperature at 2000 r / min for 2 h, and finally placed in a 150°C drying oven for 48 h to obtain water-resistant spherical aluminum nitride-boron nitride composite powder (the mass ratio of spherical aluminum nitride-boron nitride composite powder, dodecyltrimethoxysilane, distilled water, and polyolefin is 800:6:6:6).
[0028] Comparative Example 1 The aluminum nitride-boron nitride precursor slurry in step (1) of Example 1 is replaced with a slurry mixed with irregular aluminum nitride, flaky boron nitride, yttrium aluminate, and distilled water. The mass of each component in the slurry is the same as in Example 1, and the subsequent steps are the same as in Example 1.
[0029] Comparative Example 2 The method and steps of Example 1 are basically repeated, except that aluminum nitrate and nano carbon black are not added in step (1).
[0030] Comparative Example 3 The method and steps of Example 1 are basically repeated, except that yttrium aluminate is not added in step (1).
[0031] Comparative Example 4 The method and steps of Example 1 are basically repeated, except that: N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane and polyamide are not added in step (3).
[0031] The performance test methods and standards are as follows: Maximum filling number test: After 90g of 10000cP epoxy resin and 10g of 2,4,6-tris(dimethylaminomethyl)phenol are mixed evenly, a certain amount of powder fillers of the embodiments of the present invention and the comparative example are added, and after preliminary dispersion, they are placed in a vacuum stirring degassing machine with a speed set to 700r / min, stirred for 1min, and then pressed and shaped into a cured sheet with a thickness of 2mm by a molding machine. The cured sheet is placed in a 120°C oven and dried for 0.5h. The cured sheet is taken out and naturally cooled to room temperature. The maximum filling number is reached if the cured sheet does not fall off and the surface does not crack. Hydrolysis resistance pH change test: Pour 10g powder into a 500mL beaker, add 5g ethanol, stir evenly, then add 100g distilled water, stir evenly again, put the beaker into a constant temperature and humidity drying oven at 85℃ and 85%RH, test the pH value three times with a pH meter every 5h for 60h.
[0032] Table 1: Maximum filling number of spherical boron nitride prepared in each case serial number Maximum number of fillings Example 1 370 copies Example 2 350 copies Example 3 310 copies Comparative Example 1 70 servings Comparative Example 2 50 servings Comparative Example 3 50 servings Comparative Example 4 50 servings
[0033] From the attached figure and the data in Table 1, we can see that: (1) Scanning electron microscopy images ( Figure 1-4 ) analysis, comparative example 1 ( Figure 2 ) was used to carry out spherical granulation experiments with irregular aluminum nitride and flake boron nitride. After ultrasonic vibration, the particle morphology was still flake or irregular, and its pH>9, indicating that it had no hydrolysis resistance; Comparative Example 2 ( Figure 3 ) was not added with aluminum source to conduct spherical granulation experiment. After ultrasonic vibration, the particle morphology did not form a spherical shape, and pH>9, indicating that it had no hydrolysis resistance; Comparative Example 3 ( Figure 4 ) was not added with yttrium aluminate to carry out spherical granulation experiment. After ultrasonic vibration, the particle morphology did not form a spherical shape, and its pH>9, indicating that it has no hydrolysis resistance; Comparative Example 4 ( Figure 5 ) was modified without adding organic matter. After ultrasonic vibration, although the particle morphology was spherical, the particle surface was rough and had many pores, and its pH was greater than 9, indicating that it had no hydrolysis resistance. The water-resistant spherical aluminum nitride-boron nitride composite powder ( Figure 1) After ultrasonic vibration, its morphology is spherical with smooth surface and no pores, and its pH is less than 9, indicating that it is resistant to hydrolysis. (2) According to the analysis of the maximum filling ratio of the spherical boron nitride prepared in each example (Table 1), compared with Comparative Examples 1 to 4, the water-resistant spherical aluminum nitride-boron nitride composite powder Examples 1 to 3 of the present invention are more excellent in dispersion performance, and the filling ratio in 10000 cP epoxy resin can be increased by 260 to 320 parts, indicating that the water-resistant spherical aluminum nitride-boron nitride composite powder greatly improves the dispersion performance of boron nitride and its compatibility with organic resins, and greatly improves the thermal conductivity of the modified aluminum nitride-boron nitride composite material.
[0034] It can be seen from the above examples that the present invention successfully prepares water-resistant spherical aluminum nitride-boron nitride composite powder, solves the disadvantage of hydrolysis resistance in the prior art, makes the product neutral, is not easy to cause damage to equipment, and is easy to promote the process.
[0035] The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, all equivalent changes or modifications made according to the structure, characteristics and principles described in the scope of the patent application of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder, characterized in that: The following steps are involved: (1) Preparation of spherical aluminum nitride-boron nitride precursor: a boron source, an aluminum source, a carbon source, an alkaline nitrogen source, and distilled water are transferred into a stainless steel reactor lined with polytetrafluoroethylene, heated at 300-500°C for reaction for 24-72 hours, and naturally cooled to room temperature to obtain an aluminum nitride-boron nitride precursor slurry, and then a certain amount of yttrium aluminate is poured into the aluminum nitride-boron nitride precursor slurry, mixed evenly, and placed in a spray dryer for granulation to obtain a spherical aluminum nitride-boron nitride precursor; the air inlet temperature of the spray dryer is 200-350°C, the fan frequency is 20-40 Hz, the needle passing time is 1-5 s, and the peristaltic pump speed is 10-30 r / min; (2) Preparation of spherical aluminum nitride-boron nitride composite powder: Add the spherical aluminum nitride-boron nitride precursor obtained in the above (1) into a crucible, and then place the crucible in an atmosphere furnace and calcine it under nitrogen or ammonia at a calcination temperature of 1300-1700° C. for a holding time of 1-12 h; then calcine it under air at a calcination temperature of 300-600° C. for a holding time of 24-72 h. After the sintered body is naturally cooled to room temperature, it is placed in a planetary ball mill at a rotation speed of 100-300 r / min and ball milled for 5-90 min to obtain a spherical aluminum nitride-boron nitride composite powder; (3) Preparation of water-resistant spherical aluminum nitride-boron nitride composite powder: The spherical aluminum nitride-boron nitride composite powder obtained in the above (2), silane coupling agent, and distilled water are added to a 1000 mL alloy can in a certain proportion, and then placed in a high-speed stirrer, stirred and reacted at room temperature at a speed of 500 to 2000 r / min for 0.5 to 2 h, and then the resin is added to the alloy can in a certain proportion, and the stirring reaction is continued at room temperature at a speed of 500 to 2000 r / min for 0.5 to 2 h, and finally placed in a drying oven at 90 to 150° C. for 12 to 48 h to obtain a water-resistant spherical aluminum nitride-boron nitride composite powder.
2. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: In the step (1), the mass ratio of the boron source, the aluminum source, the carbon source, the alkaline nitrogen source, the distilled water and the yttrium aluminate is 3-10:1-10:3-5:3-10:10-200:0.2-5.
3. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: In the step (1), the boron source is one or more of boric acid, metaboric acid, anhydrous sodium tetraborate, sodium tetraborate pentahydrate, sodium tetraborate decahydrate, and ammonium borate.
4. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: The aluminum source in step (1) is one or more of aluminum nitrate, aluminum nitrate nonahydrate, aluminum sulfate, aluminum chloride, sodium aluminate, and potassium aluminate.
5. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: The carbon source in step (1) is nano carbon black.
6. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: In the step (1), the alkaline nitrogen source is one or more of ammonia water, cyanuric chloride, melamine, urea and imidourea.
7. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: In the step (1), the yttrium aluminate is one or more of yttrium aluminate and yttrium aluminum stone.
8. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: In the step (3), the mass ratio of the spherical aluminum nitride-boron nitride composite powder, the silane coupling agent, the distilled water and the resin is 300-800:1-6:1-6:1-6.
9. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: The silane coupling agent in step (3) is one or more of N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, dodecyltrimethoxysilane, dibutylaminomethyltriethoxysilane, 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane and 3-aminopropylmethyldiethoxysilane.
10. The method for preparing a water-resistant spherical aluminum nitride-boron nitride composite powder according to claim 1, characterized in that: The resin in step (3) is one or more of polyamide, polyolefin, polyester and epoxy resin.
Citation Information
Patent Citations
Preparation method of aluminum nitride / boron nitride composite ceramic powder
CN104725049A
Preparation method of boron nitride-aluminium nitride composite powder
CN109384468A